Megarectosigmoid in anorectal malformations: the role of laparoscopic resection - Dalmonte, Giorgio; Mita, Maria Teresa; Lombardi, Laura; Scarpa, Alberto Attilio; Del Rossi, Carmine; Cecchini, Stefano; Marchesi, Federico (Acta Biomedica Atenei Parmensis, 2019)
Surgical treatment for anorectal malformations may lead to chronic constipation or stool incontinence. The first condition is mostly linked to an abnormal dilation of rectum and sigma and it is primarily managed with medical therapy (laxatives, diet and enemas). When medical therapy fails to improve the symptoms, a surgical resection of the dilated colon is advocated. When performing the procedure it is mandatory to consider all the previous operations the patient undergone. We present a laparoscopic left emicolectomy for an extremely dilated megarectosimoid after posterior sagittal anorectoplasty in childhood for a recto-urethral fistula.